PENINGKATAN KUALITAS KOMPETENSI GURU BK SEBAGAI KONSELOR DI SEKOLAH DALAM MENGHADAPI TANTANGAN GLOBAL - Zaini Dahlan (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
The counselor's knowledge competence includes knowledge of What is a counselor's supervisor, the requirements for a counselor's supervisor, the counselor's principal duties, the counselor's supervisory function, and the right and authority of a counselor's supervisor. Personality competence is the ability, skill and skill that a person displays. Foker states that "the personality competencies possessed by counselors are spirited educators, open, able to develop themselves and have the integrity of personality". The personality competencies that the counselor must possess are open-minded educators, able to develop themselves and have personality integrity. Counselors must have an open mind and be able to control themselves. The personality of the counselor involves things like value, work spirit, nature or characteristics, and behavior. Professionalism of a teacher is a necessity in realizing a knowledge-based school, which is an understanding of learning, curriculum, and human development including learning styles. Professional counselors provide services in the form of counseling (advocacy) coordination, collaborate and provide consultation services that can create equal opportunities in achieving opportunities and success for the counselee based on the principles of profesionaitas.Keyword: Competence, counsel teacher, global